Clinical manifestations associated with acute viral gastroenteritis pathogens among pediatric patients in Qatar. Issue 8 (19th February 2021) - Abdel‐Rahman, Manar E.; Mathew, Shilu; Al Thani, Asmaa A.; Ansari, Khalid Al; Yassine, Hadi M.
Abstract: Background: Acute gastroenteritis (AGE) remains a significant cause of diarrhea that affects children worldwide. It is usually caused by viral agents, including rotavirus (RV), norovirus (NoV), adenovirus (AdV), astrovirus (AstV), and sapovirus (SaV), and the disease severity varies accordingly. Here, we report the association of clinical severity among AGE‐infected pediatrics caused by a single viral pathogen, coinfection (viral–viral), mixed infection (viral–bacterial), and AGE‐negative samples. Methods: A total of 901 pediatric patients were admitted with AGE to the Pediatric Emergency Center of Hamad Medical Corporation in Qatar from June 2016 to June 2018. The age of the subjects ranged between 3 months and 14 years (median of 16 months). Virus antigens detection was performed by using Film Array Gastrointestinal (GI) Panel kit. AGE severity was assessed using the Vesikari Clinical Severity Scoring System. Multivariable multinomial logistic regression was used to model the five AGE viral agents' likelihood in relation to severity versus co‐infection, mixed infection, and AGE‐negative samples. Results: AGE was most common in pediatrics aged 1–3 years (median age = 1.25 years) and more frequent in males than females, with a ratio of 1:0.8. About 19.2% of the infections were caused by NoV, followed by RV (18.2%), AdV (6.5%), SaV (2.3%), and AstV (1.8%). The majority of viral agents were detected higher in mixed infection (32.1%) than coinfection (4.9%). Based on the Vesikari score system, severe clinical illness was recorded among pediatrics infected with RV (82.2%) and NoV (75.7%). Further on multivariable analysis, compared to testing negative, the odds of detecting RV was three times significantly higher in children with severe symptoms relative to those with moderate (adjusted‐odds ratio [a‐OR] = 3.10; 95% confidence interval [CI] = 1.82–5.28). Similar results were observed when considering RV relative to co‐infection and mixed infection (a‐OR = 2.59; 95% CI = 1.23–5.48 and a‐OR = 2.06; 1.28–3.30, respectively). About one‐third of the study sample were Qatari children with AGE (33%), whereas 35% and 32% were pediatrics from the Middle East and North Africa region, excluding Qatari and nonregions. Conclusion: This study underlines the association of disease severity among AGE‐infected pediatrics in Qatar. The overall Vesikari median score was significantly high, followed by more frequent hospitalization among RV‐infected pediatrics compared to others. There was no reduction in the disease severity among RV‐infected regardless of the vaccine dose.